Pengembangan Perangkat Pembelajaran Berbasis Deep Learning pada Topik Sistem Pencernaan Manusia untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V di SDN Tegal Besar 03 - Diah Alfian Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the curriculum’s requirement to prepare students capable of understanding concepts in depth and by the low level of students’ conceptual understanding of the topic of the Human Digestive System. The learning process tends to focus on memorizing concepts and assigning tasks, and does not sufficiently involve students in the learning process. This study aims to develop a deep learning-based instructional tool that is valid, effective, and practical in improving the learning outcomes of fifth-grade students at SDN Tegal Besar 03 on the topic of the Human Digestive System. Validity was measured based on expert validation covering graphic, content, and language aspects. Effectiveness was measured using the N-Gain test, and practicality was measured using the SAS test. This study employed the ADDIE model with a pre-experimental research design using a one-group pretest-posttest design. The results showed that the deep learning-based instructional materials developed had a validity level of 88.106 (highly valid), an effectiveness level of 80 (effective), and a practicality level of 85.952 (highly practical). Therefore, these deep learning-based instructional materials are suitable for use in improving student learning outcomes and supporting the creation of deep learning experiences tailored to students’ needs.
FINALISASI oleh Arif 2026 Juni 23
Keywords: Instructional Tools; Deep Learning